(untitled) (American Journal of Pedagogical and Educational Research, 2024)
History shows that the processes of borrowing have come a long way. This is confirmed, for example, by a large number of borrowings from Latin and other ancient languages. In the context of globalization, these processes occur continuously and at great speeds. Thus, a huge number of borrowed words appear, which adapt to the grammatical norms of the recipient language and after a while cease to be perceived as "non-native" words does not always happen. Some words remain alien elements, not included in the active vocabulary of the language.